Can forest carbon sequestration offset industrial CO2 emissions? A case study of Hubei Province, China - Cheng, Jing; Huang, Chunbo; Gan, Xintao; Peng, Changhui; Deng, Lei (Journal of Cleaner Production, 2023)

Effects of vegetation restoration on soil nutrients, plant diversity, and its spatiotemporal heterogeneity in a desert–oasis ecotone - Wu, Chunyan; Deng, Lei; Huang, Chunbo; Chen, Yongfu; Peng, Changhui (Land Degradation & Development, 2021)
Abstract Vegetation restoration has been proposed as an effective measure for rehabilitating degraded land and slowing desertification in arid regions. However, the spatial variation in soil quality and plant diversity following vegetation restoration remains unclear. This study was designed to explore soil nutrient dynamics and how soil nutrients affect plant diversity and spatial heterogeneity after shrub restoration. We assessed the effect of Haloxylon ammodendron (C.A.Mey.) Bunge (which has been planted over 30 years) on the soil nutrients and plant diversity in a desert–oasis ecotone in Minqin County, Gansu, China, using geostatistics, beta diversity and rarefaction analyses, and Hill number extrapolation. Soil nutrients, including soil organic matter, total nitrogen, and alkali nitrogen, increased significantly after H. ammodendron planting. Species richness gradually increased from 1–5 years to 10–20 years after H. ammodendron was planted but then decreased at 20–30 years. The largest differences in plant composition were observed at 15 and 20 years. Plant diversity increased in the whole 30 years after shrub planting, increasing in the first 25 years and then decreasing at 26–30 year stage. The maximum coefficient of determination for the spatial heterogeneity model fit was 0.84 (25 years). The spatial heterogeneity in vegetation decreased with increasing soil available K content at 1–10 years. Our results suggest that planting shrubs can improve soil conditions and plant species diversity in desert–oasis ecotones and soil nutrients have a strong influence on plant diversity patterns and spatial heterogeneity following vegetation restoration.

Impacts of environmental and socioeconomic factors on gross ecosystem product of the Three Gorges reservoir area, China - Cheng, Jing; Liu, Shuangshuang; Huang, Chunbo; Wang, Lunche; Liu, Zelin; Peng, Changhui (Land Degradation & Development, 2024)
Abstract Environmental and socioeconomic drivers would alter landscapes, bringing various effects with different directions and magnitudes. Demonstrating these driving effects is key to relieving the conflicts between territorial vegetation restoration and regional economic growth. However, the relationship between ecological protection and economic development due to landscape dynamics has not been systematically demonstrated as environment is difficult to quantify by the monetary value. In this article, we explored the changes in gross ecosystem product (GEP) in the Three Gorges (TG) reservoir area and constructed a conceptual framework to explicate its driving mechanism. Our results suggested that topographic, soil, and climatic factors positively impact on GEP through their important effects on vegetation structure, distribution, and succession. Additionally, reforestation policies promote the conversion of farmland and grassland to forestland in the TG reservoir region, which was the main contributor to enhancing GEP. Conversely, socioeconomic factors negatively impact GEP, of which effects were mainly manifested by changes in the proportion of ecological land. Therefore, it is essential to maintain a suitable land use proportion in this region to optimize GEP, and we proposed a landscape restoration program to enhance four ecosystem productions. This article provides a reference for land resource allocation for environmental protection and sustainable development in ecologically fragile areas.

The effects of elevated CO2, elevated O3, elevated temperature, and drought on plant leaf gas exchanges: a global meta-analysis of experimental studies - Zhang, Jinmeng; Deng, Lei; Jiang, Hong; Peng, Changhui; Huang, Chunbo; Zhang, Minxia; Zhang, Xiuying (Environmental Science and Pollution Research, 2021)

Impacts of landscape dynamics on terrestrial ecosystem health in the Three Gorges Reservoir Area, China - Huang, Chunbo; Cheng, Jing; Liu, Shuangshuang; Wan, Yunshan; Zhou, Jie; Liu, Zelin; Peng, Changhui (Journal of Cleaner Production, 2024)

Soil GHG fluxes are altered by N deposition: New data indicate lower N stimulation of the N2 O flux and greater stimulation of the calculated C pools - Deng, Lei; Huang, Chunbo; Kim, Dong‐Gill; Shangguan, Zhouping; Wang, Kaibo; Song, Xinzhang; Peng, Changhui (Global Change Biology, 2020)
Abstract The effects of nitrogen (N) deposition on soil organic carbon (C) and greenhouse gas (GHG) emissions in terrestrial ecosystems are the main drivers affecting GHG budgets under global climate change. Although many studies have been conducted on this topic, we still have little understanding of how N deposition affects soil C pools and GHG budgets at the global scale. We synthesized a comprehensive dataset of 275 sites from multiple terrestrial ecosystems around the world and quantified the responses of the global soil C pool and GHG fluxes induced by N enrichment. The results showed that the soil organic C concentration and the soil CO 2 , CH 4 and N 2 O emissions increased by an average of 3.7%, 0.3%, 24.3% and 91.3% under N enrichment, respectively, and that the soil CH 4 uptake decreased by 6.0%. Furthermore, the percentage increase in N 2 O emissions (91.3%) was two times lower than that (215%) reported by Liu and Greaver ( Ecology Letters , 2009, 12:1103–1117). There was also greater stimulation of soil C pools (15.70 kg C ha −1 year −1 per kg N ha −1 year −1 ) than previously reported under N deposition globally. The global N deposition results showed that croplands were the largest GHG sources (calculated as CO 2 equivalents), followed by wetlands. However, forests and grasslands were two important GHG sinks. Globally, N deposition increased the terrestrial soil C sink by 6.34 Pg CO 2 /year. It also increased net soil GHG emissions by 10.20 Pg CO 2 ‐Geq (CO 2 equivalents)/year. Therefore, N deposition not only increased the size of the soil C pool but also increased global GHG emissions, as calculated by the global warming potential approach.

Drought effects on soil carbon and nitrogen dynamics in global natural ecosystems - Deng, Lei; Peng, Changhui; Kim, Dong-Gill; Li, Jiwei; Liu, Yulin; Hai, Xuying; Liu, Qiuyu; Huang, Chunbo; Shangguan, Zhouping; Kuzyakov, Yakov (Earth-Science Reviews, 2021)